Glomalin contributed more to carbon, nutrients in deeper soils, and differently associated with climates and soil properties in vertical profiles. Issue 1 (December 2017) - Wang, Wenjie; Zhong, Zhaoliang; Wang, Qiong; Wang, Humei; Fu, Yujie; He, Xingyuan
Abstract Despite vital importance in soil conditioning and a proxy for arbuscular mycorrhizal (AMF), glomalin-related soil protein (GRSP) contribution to soil carbon and nutrients at vertical soil profiles and underlying mechanism were not well-defined yet. Thus, 360 soil samples were collected from 72 farmland 1-m soil profiles in northeastern China, and soil physiochemical properties, nutrients, glomalin characteristics, local climates were determined. Linear decreases of glomalin amounts were observed from the top to deep soils, and glomalin/SOC (glomalin ratio to total SOC) in the 80–100 cm soil (EEG, easily-extracted GRSP, 2.2%; TG, total GRSP, 19%) was 1.34–1.5-fold higher than did in the 0–20 cm soil. Different statistical analyses crosschecked that the lower pH and higher SOC usually accompanied with the higher EEG and TG, while EEG was more sensitive to climates; Moreover, glomalin was more physiochemical-regulated in the deep soils, but more nutrient-regulation was found in the surface soils. Structure Equation Model showed that soil depths and climates indirectly affected TG and EEG features through soil properties, except significant direct effects on EEG. In future, glomalin assessment should fully consider these for identifying the AMF importance in the whole 1-m profile, and our findings also favor degrade soil improvement from glomalin rehabilitation.